FIXED DOSE COMBINATION OF MECOBALAMIN AND PREGABALIN IN THE TREATMENT OF OROFACIAL NEUROPATHIC PAIN - Manuel Dwiyanto Hardjo Lugito (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: orofacial neuropathic pain is extraordinary disease in character with its complicated management. Mecobalamin has been used to provide regeneration of traumatized nerves. Pregabalin with its analgesic activities relieves the clinical signs of neuropathic pain. The aim of this case report is to explain fixed dose combination of Mecobalamin and Pregabalin as the treatment of neuropathic pain caused by inferior alveolar nerve and facial nerve neuropathy. Case: First case was an inferior alveolar nerve neuropathy experienced by 63 years old female with complaints of persistent pain and numbness around the left chin and left lower lip the day following the procedure of surgery for the treatment of dentoalveolar abscess on left second premolar of mandibula. Second case was facial nerve neuropathy experienced by 54 years old female had persistent pain and numbness of the anterior two-thirds of the tongue after total thyroidectomy and 1,100 MBq (30 mCi) activity of Radioactive iodine (RAI) therapy, followed with two 131I whole body scans. Case Management: Mecobalamin 500 µg and Pregabalin 75 mg twice daily for 5 weeks were given with tolerable side effects and improvement symptoms. Discussion: Pregabalin combined with Mecobalamin can reduce orofacial neuropathic pain. Pregabalin possess analgesic property and reduce neuropathy-related pain symptoms while Mecobalamin facilitates myelinogenesis and nerve regeneration. Conclusion: Fixed Dose Combination of Mecobalamin and Pregabalin has the potential analgesic effect, reduced neuropathic orofacial pain at a below than determined dosage in case of inferior alveolar and facial nerve neuropathic pain.